The effect of waste cooking oil methanol molar ratio on yield and properties of biodiesel produced in a mini plant - Abdullah, Noor Hazwani (2017)
Azhar food factory used a lot of cooking oil at least 144 tonne per year for frying and the company produce waste cooking oil about 54 tonne per year and WCO need to dispose in a suitable way without harming the environment. One of the alternative methods proposed is by converting the WCO into biodiesel. A mini plant to produce biodiesel from waste cooking oil was been design, fabricated and installed at the factory. Biodiesel from WCO are difficult and costly when free fatty acid content more is than 2%. There are some problems of WCO such that it can lead to pollution and health risk. Therefore, this research were carried out to propose a simple small pilot plant to produce biodiesel using WCO and to investigate the operation of the plant with WCO as input with various molar ratio which is 6:1, 9:1 and 12:1 respectively with the same parameter such as holding time of 2 hours, temperature of 600C and 600 rpm agitation speed. The properties of biodiesel such as Free Fatty Acid (FFA), water content, flash point, acid value, density, kinematic viscosity, and moisture content was investigated to fulfil standard ASTM D7461 and EN14013 Fatty Acid Methyl Ester to determine yield of biodiesel using GC-FID. The FAME value of molar ratio 6:1 is 97.8% meanwhile molar ratio 9:1 value is 97.2 % and molar ratio 12:1 is 95.7% has been achieved. Evaluation and comparison between five percent biodiesel from the plants and B5 petroleum diesel with standards ASTM D975. In this process were made molar the ratio of alcohol 12:1 cost very high is RM421.60, meanwhile molar ratio 9:1 cost RM329.60 and 6:1 molar ratio cost RM246.96. The best yield of methyl ester from waste cooking oil is 6:1 From the result above it can be concluded that the produced WCO-Biodiesel has achieved the standards because it fulfilled ASTM D7461 and EN 14131 standard.